Exploring the Impact of Transformational and Transactional Style of Leadership on Nursing Care Performance and Patient Outcomes - Al-Rjoub S; Alsharawneh A; Alhawajreh MJ; Othman EH (Journal of Healthcare Leadership)
Saleem Al-Rjoub,1 Anas Alsharawneh,2 Mohammad J Alhawajreh,3 Elham H Othman4 1Department of Community & Mental Health Nursing, Faculty of Nursing, The Hashemite University, Zarqa, Jordan; 2Department of Adult Health Nursing, Faculty of Nursing, The Hashemite University, Zarqa, Jordan; 3Health Services Management Department, Middle East University, Amman, Jordan; 4Faculty of Nursing, Applied Science Private University, Amman, JordanCorrespondence: Saleem Al-Rjoub, Email saleemf@hu.edu.joBackground: The form of leadership that can positively influence nursing care performance and patient outcomes remains a crucial subject in the healthcare sector.Aim: This study examines the effect of leadership style at different managerial levels on nursing care performance and patient outcomes.Methods: A retrospective cohort study was conducted in a public hospital, focusing on two primary settings: the general ward and the critical care unit. The study sample included 60 nurses and 300 patients. The leadership style is a predictor of this study and was measured using a cross-sectional survey of Jordanian nurses using the Multifactor Leadership Questionnaire (MLQ). Nursing care performance and patient outcomes were measured by surveying patients, observing practice, and reviewing health records. The analysis involved descriptive statistics, chi-square tests, odds ratios, and multivariate regression analysis.Results: The study found that transformational leadership was predominant in the general ward, while transactional leadership was more common in the critical care unit. Leadership styles significantly influence clinical nursing performance. Nurses under transformational leaders were more likely to follow generic policies like patient surveillance but less consistent with specific care standards. Nurses under transactional leaders were linked to higher adherence to standardized care protocols like fall risk assessment and medication rights. Patient outcomes were similar between units, except for higher readmission rates under transactional leadership.Conclusion: The study’s findings underscore the complexities of nurse leadership styles and clinical nursing performance. Nurse manager should adapt their leadership style to the particular setting and a one-size-fits-all approach to leadership may not be effective in healthcare.Keywords: nursing leadership, transformational leadership, transactional leadership, nurse manager, patient outcome, nursing care performance